Development of a smarter and greener charging station for EVs and PMDs - Aw, Orlando Hong Xian (Nanyang Technological University, 2020)
Energy and transport are huge part of society now. Amidst the climate change worsening, the world must find a cleaner source of energy to power our lives now. Thus, the adoption of Solar Photovoltaic Systems and Electric Vehicles (EV) are increasing an important step towards this goal. At least 10 countries have pledged to fully embrace the electrification of transport in the next 3 decades, but the lack of charging stations around the world is impeding the proliferation of EVs. But an electric vehicle is not totally clean and green if the power it is using is derived from fossil fuel. This project is about designing a cleaner and greener EV charging station. It seeks to make charging stations greener by attributing some of the energy it uses to energy that is produced by solar PV system. It also makes the system smarter by creating a platform that can enable users to reserve in advance. The novelty of this project report is to design a monitoring system using Raspberry Pi as the datalogger. It will get data from Solar Inverters, Power meters and Pyranometer. The data will be sent to Google Cloud Firestore to be displayed on a frontend dashboard Powermon. An EV charging station will also designed using Open Charge Point Protocol (OCPP) as a central management system. Lastly, a mobile application will be developed to remotely monitor and manage the charging of their EV via a mobile app. The data from the Solar monitoring system will be used to report the how much of the energy used to charge the EV came from solar energy.